Determinants of choice in the form of conducting municipal economy by local government units - Kosek-Wojnar, Maria; Maj-Waśniowska, Katarzyna (Journal of Public Governance, 2019)
Objectives: This paper aims to address a problem that includes the managing of the municipal economy by local government units (LGUs). The research issue raised regarded, in particular, the rules and organisational-legal norms for managing a municipal economy. Its expression is the posed hypothesis according to which what matters significantly for LGUs in the choice of form for conducting a municipal economy is both the character of the task as well as whether this form is recognised as a subject of the public finances sector, and, what follows, whether its indebtedness is subject to statutory restrictions and influences the financial situation of LGUs. Research Design & Methods: To verify a hypothesis formulated in such a way, firstly theoretical and legal aspects of managing a municipal economy by LGUs have been put forward. Next a comparative analysis for forms of managing a municipal economy by LGUs was conducted, i.e. a local self-government budgetary establishment and a municipal company, and the most significant characteristics of the discussed forms, as well as their effects being a result of their choice by LGUs, were indicated. Comparative and descriptive analysis has been used in this paper; it included analysis of financial data regarding the management of a municipal economy by LGUs, but in strict correlation with institutional and legal conditions for the realisation of public tasks and their conditioning. Findings: As a result of the research conducted, it has been concluded that changes taking place in the scope of forms of managing a municipal economy point towards more and more common tasks realised by LGUs both in the field of public utility as well as outside of the public utility zone in the form of commercial law companies. Contribution: Basic kinds of risks associated with the realisation of tasks by the budgetary establishment and municipal company have also been defined. Moreover, research results show that possibilities for such a wide operation result first and foremost from imprecise legal regulations, which are at the same time the only source of risk associated with the operation of such companies.